Will an app-based reading intervention change how teachers rate their teaching self-efficacy beliefs? A test of social cognitive theory in Swedish special educational settings - Reichenberg, Monica; Thunberg, Gunilla; Holmer, Emil; Palmqvist, Lisa; Samuelsson, Jenny; Lundälv, Mats; Mühlenbock, Katarina; Heimann, Mikael (Frontiers in Education, 2023)
Educational researchers have challenged Bandura’s prediction that self-efficacy beliefs tend to be established early in learning and that once set, self-efficacy beliefs persist unless a critical event causes them to be reevaluated. However, the results have been mixed in previous research, including being positive, negative, and unchanged. In response, we evaluated how 75 teachers (i.e., special educators) rate their teaching self-efficacy beliefs in motivating student reading and adapting reading instruction at two time points. All teachers taught students with an intellectual disability, communication difficulties, and poor reading skills. The teachers participated in a workshop to learn teaching reading strategies with apps under various conditions (comprehension strategies, phonemic strategies, or both comprehension and phonemic strategies). We analyzed teacher self-efficacy beliefs at two time points with a 12-week span (pre-and postintervention). First, we developed measures of teacher self-efficacy through confirmatory factor analyses. Next, we analyzed the data with multiple imputation and mixed linear regression with difference-in-differences (DiD). The results indicated no statistically significant treatment effect on teachers’ rating of their teaching self-efficacy beliefs. We conclude that our results agree with Bandura’s original prediction and thus, his social cognitive theory.